EVALUASI KAPASITAS DAYA DUKUNG AKSIAL DAN LATERAL HELICAL PILE MENGGUNAKAN METODE EMPISRIS DAN ANALISIS BATAS TERADAP HASIL PENGUJIAN AKSIAL DAN LATERAL DI LAPANGAN - Farian Albajili; Muhamad Yusa; Ferry Fatnanta (Racic : Rab Construction Research, 2026)
The construction of deep foundations in operational industrial facilities faces challenges due to the presence of existing buildings and active machinery. Helical piles offer a stable, environmentally friendly, and vibration-free solution that is safe for surrounding structures. This study compares the results of empirical methods and limit analysis in the design of helical piles with field test results of axial loads. The research began with the collection and correction of Standard Penetration Test (SPT) data to a depth of 15 m to determine soil technical parameters. Based on these data, helical pile models with various design configurations were analyzed using empirical methods, limit analysis, and field testing. The results indicate that limit analysis provides axial load capacities that are closer to field test results compared to other empirical methods. The highest capacity was obtained for pile type D1-H1-S1-M piles, which have larger helix and shaft diameters, while differences in test locations meant that pile type D2-H2-S3-SH piles could not be directly compared to the others